Combining Climate Smart Agriculture Practises Pays Off: Evidence on Food Security From Southern Highland Zone of Tanzania - Bongole, Abiud J.; Hella, Joseph P.; Bengesi, Kenneth M. K. (Frontiers in Sustainable Food Systems, 2022)
Concerns of food insecurity and climate change are serious global challenges, Tanzania included. In response, farm households are using various climate-smart agricultural practises (CSA-practises) which are believed to play a vital role to increase agricultural productivity, increasing resilience to climate change, and reducing mitigation costs for greenhouse gas (GHG) emissions while improving households' food security. Despite these benefits of CSA-practises but the usage of these practises is still voluntary and its impact on household welfare specifically food security is not well-documented in Tanzania, particularly in Mbeya and Songwe Region. Therefore, the determinants of using CSA-practises (in particular organic manure, drought-tolerant maize seeds, and irrigation) and the impact of the usage of household food security was examined. The cross-sectional study design was used to collect information from farming households in the Southern Highlands of Tanzania (Mbeya and Songwe regions). To evaluate the impact of the combination of CSA-practises on household food security the study used a multinomial endogenous treatment effect model. A counterfactual analysis was conducted to compare the impacts from different combinations of CSA-practises considered. The findings show that household, plot, and institutional characteristics have significant effects on the usage of a different combination of CSA-practises. The study also found that the highest payoff of food security is achieved when CSA-practises are used in combination rather than in isolation. The package that contains a combination of drought-tolerant maize seeds and Irrigation (Or0Dt1Ir1) gave a higher payoff than the combination of all three CSA-practises. The study suggests that based on the practises considered in this study, the usage of a combination of various practises results in better food security compared to the usage of these practises individually. This indicates that promoting a combination of CSA-practises could enhance household food security.